Radiation dosimetry in magnetic fields with Farmer-type ionization chambers: determination of magnetic field correction factors for different magnetic field strengths and field orientations. (1st August 2017) - Spindeldreier, C K; Schrenk, O; Bakenecker, A; Kawrakow, I; Burigo, L; Karger, C P; Greilich, S; Pfaffenberger, A
Abstract: The aim of this work was to determine magnetic field correction factors that are needed for dosimetry in hybrid devices for MR-guided radiotherapy for Farmer-type ionization chambers for different magnetic field strengths and field orientations. The response of six custom-built Farmer-type chambers irradiated at a 6 MV linac was measured in a water tank positioned in a magnet with magnetic field strengths between 0.0 T and 1.1 T. Chamber axis, beam and magnetic field were perpendicular to each other and both magnetic field directions were investigated. EGSnrc Monte Carlo simulations were compared to the measurements and simulations with different field orientations were performed. For all geometries, magnetic field correction factors, k B Q, and perturbation factors were calculated. A maximum increase of 8.8% in chamber response was measured for the magnetic field perpendicular to chamber and beam axis. The measured chamber response could be reproduced by adjusting the dead volume layer near the chamber stem in the Monte Carlo simulations. For the magnetic field parallel to the chamber axis or parallel to the beam, the simulated response increased by 1.1% at maximum for field strengths up to 1.1 T. A complex dependence of the response was found on chamber radius, magnetic field strength and orientation of beam, chamber axis and magnetic field direction. Especially for magnetic fields perpendicular to beam and chamber axis, the exact sensitive volume has to be considered in the simulations. To minimize magnetic field correction factors and the influence of dead volumes on the response of Farmer chambers, a measurement set-up with the magnetic field parallel to the chamber axis or parallel to the beam is recommended for dosimetry.